Taxonomy and pathogenicity of fungi associated with oak decline in northern and central Zagros forests of Iran with emphasis on coelomycetous species - Bashiri, Samaneh; Abdollahzadeh, Jafar (Frontiers in Plant Science, 2024)
Oak decline is a complex disorder that seriously threatens the survival of Zagros forests. In an extensive study on taxonomy and pathology of fungi associated with oak decline in the central and northern part of Zagros forests, 462 fungal isolates were obtained from oak trees showing canker, gummosis, dieback, defoliation, and partial or total death symptoms. Based on inter-simple sequence repeat (ISSR) fingerprinting patterns, morphological characteristics, and sequences of ribosomal DNA (28S rDNA and ITS) and protein coding loci (acl1, act1, caM, tef-1α, rpb1, rpb2, and tub2), 24 fungal species corresponding to 19 genera were characterized. Forty percent of the isolates were placed in eight coelomycetous species from seven genera, namely, Alloeutypa, Botryosphaeria, Cytospora, Didymella, Gnomoniopsis, Kalmusia, and Neoscytalidium. Of these, four species are new to science, which are introduced here as taxonomic novelties: Alloeutypa iranensis sp. nov., Cytospora hedjaroudei sp. nov., Cytospora zagrosensis sp. nov., and Gnomoniopsis quercicola sp. nov. According to pathogenicity trials on leaves and stems of 2-year-old Persian oak (Quercus brantii) seedlings, Alternaria spp. (A. alternata, A. atra, and A. contlous), Chaetomium globosum, and Parachaetomium perlucidum were recognized as nonpathogenic. All coelomycetous species were determined as pathogenic in both pathogenicity trials on leaves and seedling stems, of which Gnomoniopsis quercicola sp. nov., Botryosphaeria dothidea, and Neoscytalidium dimidiatum were recognized as the most virulent species followed by Biscogniauxia rosacearum.